A New Algorithm for Solving Linear Bottleneck Assignment Problem - Pundir, Pramendra Singh; Porwal, Sandeep Kumar; Singh, Brijesh P (Journal of Institute of Science and Technology, 2015)
Linear bottleneck assignment problems have wide range of applications in emergency situation like call for fire fighters, ambulances etc. This paper presents a new simple but faster algorithm for solving linear bottleneck assignment problems, so that in such emergent situation efficient and faster decision taking could be make possible. Some examples are also discussed to explain the procedure. Journal of Institute of Science and Technology, 2015, 20(2): 101-102